Isolation and characterization of acid and pepsin soluble collagen extracted from sharpnose stingray (Dasyatis zugei) skin - Shaik, M. I. (2023)
This study aimed to isolate and characterize the acid soluble collagen (ASC) and pepsin soluble collagen (PSC) from the skin of the sharpnose stingray (Dasyatis zugei). Isolated ASC and PSC were subjected to chemical and physical characterizations. The yield of PSC (34.84±1.26%) was significantly higher than that of ASC (20.48±4.41%) (p<0.05). There were no significant differences between ASC and PSC in terms of chemical composition (p>0.05). Both ASC and PSC were thermally stable at high temperatures, with denaturation temperatures of 24.1°C and 25.2°C, respectively, and maximum temperatures of 31.94±0.13°C and 31.79±0.23°C, respectively. Fourier transform infrared (FTIR) investigations showed the presence of triple helical structure with strong hydrogen bonding in both ASC and PSC. Meanwhile, both collagens were highly solubilized at acidic pH but at different optimal pH. The surface morphologies of ASC and PSC were loose and possessed slender, less uniform and irregular fibrous network structures with large and irregular pores observed between the fibrils. This finding showed that the alternative source of marine collagen possesses good physicochemical properties which highly potential for nutraceutical, pharmaceutical or cosmeceutical application.